On Shock Reflections in Fast Flames - Logan, Maley (Université d'Ottawa / University of Ottawa, 2015)
The present work investigates the structure of supersonic turbulent deflagration typically observed as precursors to the onset of detonation. These high-speed flames are obtained after detonation interaction with cylindrical obstacles. Two mixtures having the same propensity for local hot spot generation were used, namely stoichiometric hydrogen-oxygen and methane-oxygen. It was shown that the methane mixture sustained turbulent fast flames, while the hydrogen mixture did not. Three visualization techniques, Schlieren, shadowgraph, and direct chemi-luminescence were implemented to record the evolution of the structure following the detonation interaction with the obstacle. Detailed high-speed visualizations of the nearly two-dimensional flow fields permitted the identification of the key mechanism involved. It was found that the shock reflections in methane permitted strong forward jets behind periodically formed Mach shocks on the front of the deflagration. These hot spots in the re-circulation zones of the jets provided local enhancement of the reactivity through mixing, supporting the formation of new generations of new hot spots. The hot spot formation was identified as the prominent difference between the different mixtures. These reactive pockets further sustained the shock reflection processes. As the methane-oxygen fast flame propagates along the channel, the wave front was observed to organize into fewer modes and eventually led to a reflection capable of the transition to detonation. In the hydrogen mixtures, at similar thermo-chemical parameters, self-sustained fast flames were not observed. Following detonation interaction in the hydrogen mixture, reactive reflections were observed. As the wave propagated downstream after a limited number of reactive reflections, the wave developed a planar wave front and decayed as the reaction zone trailed with an ever-increasing distance. It is postulated that the absence of the forward jets did not allow such fast flames to establish. This jetting slip line instability in methane shock reflections was recently found to be correlated with the low value of the isentropic exponent and its control of Mach shock jetting described by Mach & Radulescu. The lack of the forward jetting of the slip line in the hydrogen mixture with the higher value of the isentropic exponent is in agreement with the Mach & Radulescu.
Keywords: Detonation; Fast Flame; High Speed Deflagration; Turbulent Deflagration; Shock Reflection; Detonation Initiation